ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL TKA MATEMATIKA TINGKAT SMA DI SMAS PRIMA TEMBUNG - Agnes Venita Gultom; Manalu, Eka Novayanti; Elsa Noviyanti Br Sinaga; Maysaroh Pos Pos; Melisa Yessi Sagala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students’ ability to solve high school-level mathematics Academic Ability Test (TKA) questions at SMAS Prima Tembung. The study employed a qualitative descriptive method with a sample of 28 twelfth-grade students. Data collection was conducted by administering a mathematics TKA test consisting of 25 questions categorized into LOTS (Lower Order Thinking Skills), MOTS (Middle Order Thinking Skills), and HOTS (Higher Order Thinking Skills). The results indicated that the students’ average score was 69.42, placing them in the moderate category. Most students were able to solve LOTS questions well, but still experienced difficulties in solving MOTS and HOTS questions, which require analytical, reasoning, and problem-solving skills. The highest error rates were found in the topics of linear programming, geometric transformations, trigonometric function graphs, compound interest, the law of cosines, and circle equations. Students’ difficulties stemmed from a lack of conceptual understanding, carelessness in calculations, difficulty determining solution strategies, and low reasoning skills in solving contextual problems. Therefore, more innovative learning strategies and continuous HOTS-based practice are needed to improve students’ mathematical thinking skills.